Synchronous breast and colon cancer: the importance of multidisciplinary team cancer meetings. Issue 12 (4th December 2019) - Abdulla, Hussain Adnan; Almarzooq, Raed; Alrayes, Amal
Abstract : A 58-year-old female patient presented with left breast lump. Mammography and ultrasonography were performed, which reported lesions suspicious of malignancy in the left breast and axilla. Core biopsy of the lesions revealed invasive ductal carcinoma with axillary lymph node metastasis. Staging CT scan (thorax, abdomen and pelvis) identified a coexisting neoplasm in the ascending colon. Colonoscopy was performed and the tumour in the ascending colon was biopsied. Histopathological examination revealed adenocarcinoma. In the multidisciplinary team cancer meeting, it was decided to treat the breast cancer first and then the colon cancer, followed by adjuvant chemotherapy. In the first operation, left modified radical mastectomy was performed. Two weeks after her initial operation, the patient underwent laparoscopic right hemicolectomy. Postoperatively, the patient did not develop any complications and was referred to oncology for chemotherapy.